Pelatihan Public Speaking sebagai Upaya Pengembangan Soft Skills Guru dan Siswa English Club - Nurhayati Ganinda; Rini Lindawati; Asih Andriyati Mardliyah; Ulil Nurul Imanah (Pakis Journal Institute, 2026)
This community service program was conducted to improve the communication skills and self-confidence of teachers and English Club students at a junior high school in Sidoarjo through English public speaking training. The main challenges faced by the partner institution included low self-confidence when speaking in public, limited opportunities to practice speaking, and insufficient understanding of effective basic public speaking techniques. The program was implemented through several main stages: (1) the delivery of introductory material on public speaking, (2) training on opening and closing speech techniques, (3) pronunciation and intonation practice, (4) presentation simulations and English speech performances, and (5) the provision of feedback and mentoring throughout the activities. The results indicated an increase in participants’ active engagement, confidence in expressing their ideas in public, and ability to prepare and deliver simple speeches in English. In addition, the program enhanced participants’ motivation to develop their English communication skills more actively and continuously. This public speaking training program demonstrates that practice-based activities supported by mentoring can contribute to the development of communication-related soft skills among teachers and English Club students.